Unveiling Cassava Witches’ Broom Disease - Pardo Garcia, Juan Manuel; Cuellar, Wilmer Jose; Wei, Xiaojing; Llanos Herrera, Lizeth; Gil Ordoñez, Alejandra; Sheat, Samar; De Oliviera, Saulo; Thomas, Adele (2025)
A collection of presentations that made up a webinar that provided a comprehensive update on current knowledge of cassava witches’ broom disease in Southeast Asia and its status in South America. This information contributes to strategic collaboration and management activities.